A taxonomic review of Neogriphoneura Malloch, 1924 (Diptera: Lauxaniidae), with description of three new species - De Mello, Ramon Luciano; Silva, Vera Cristina [UNESP] (Magnolia Press, 2008)
The status of the Lauxaniidae genus Rhabdolauxania Hendel, 1925 is reevaluated and is synonymized under Neogriphoneura Malloch, 1924. Three new combinations, N. immaculata (Hendel, 1933), comb. nov., N. laevifrons (Hendel, 1925), comb. nov., and N. schnusei (Hendel, 1925), comb. nov. are proposed. Two lectotypes are designated. Three new species of Neogriphoneura are described: N. bispoi sp. nov., from Santa Catarina, Brazil, N. pacata sp. nov., from La Paz, Bolivia, and N. corrugata sp. nov. from British Virgin Islands. Illustrations of the head, wing, male and female terminalia are provided for the new species. This raises the number of species in the genus from the present five to eleven. A key is provided for the species of the genus. Copyright © 2008 Magnolia Press.
Keywords: Diptera; Lauxaniidae; Neogriphoneura; Neotropical region; New combination; New species; Rhabdolauxania